EURASIP Journal on Advances in Signal Processing - Frossard, Pascal; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The aim of the EURASIP Journal on Advances in Signal Processing is to highlight the theoretical and practical aspects of signal processing in new and emerging technologies. The journal is directed as much at the practicing engineer as at the academic researcher. Authors of articles with novel contributions to the theory and/or practice of signal processing are welcome to submit their articles for consideration. All manuscripts undergo a rigorous review process. EURASIP Journal on Advances in Signal Processing employs a paperless, electronic review process to enable a fast and speedy turnaround in the review process. The journal is an Open Access journal since 2007.
Keywords: Engineering; Quantum computers; Spintronics; Signal processing; Image processing; Speech processing systems; Engineering; Signal,Image and Speech Processing; Quantum Information Technology, Spintronics